Salivary α-amylase activity is associated with cardiometabolic and inflammatory biomarkers in overweight/obese, non-diabetic Qatari women - Al Akl, Neyla S.; Khalifa, Olfa; Habibullah, Mohammad; Arredouani, Abdelilah (Frontiers in Endocrinology, 2024)
Introduction: Obesity, prevalent in approximately 80% of Qatar's adult population, increases the risk of complications like type 2 diabetes and cardiovascular diseases. Predictive biomarkers are crucial for preventive strategies. Salivary α-amylase activity (sAAa) inversely correlates with obesity and insulin resistance in adults and children. However, the connection between sAAa and cardiometabolic risk factors or chronic low-grade inflammation markers remains unclear. This study explores the association between serum sAAa and adiposity markers related to cardiovascular diseases, as well as markers indicative of chronic low-grade inflammation.Methods: Serum samples and clinical data of 1500 adult, non-diabetic, Overweight/Obese participants were obtained from Qatar Biobank (QBB). We quantified sAAa and C reactive protein (CRP) levels with an autoanalyzer. Cytokines, adipokines, and adiponectin of a subset of 228 samples were quantified using a bead-based multiplex assay. The associations between the sAAa and the adiposity indices and low-grade inflammatory protein CRP and multiple cytokines were assessed using Pearson's correlation and adjusted linear regression.The mean age of the participants was 36 ± 10 years for both sexes of which 76.6% are women. Our analysis revealed a significant linear association between sAAa and adiposityassociated biomarkers, including body mass index β -0.032 [ 95% CI -0.049 to -0.05], waist circumference β -0.05 [ 95% CI -0.09 to -0.02], hip circumference β -0.052 [ 95% CI -0.087 to -0.017], and HDL β 0.002 [ 95% CI 0.001 to 0.004], albeit only in women. Additionally, sAAa demonstrated a significant positive association with adiponectin β 0.007 [ 95% CI 0.001 to 0.01]while concurrently displaying significant negative associations with CRP β